The role of the tumour microenvironment in immunotherapy. Issue 12 (December 2017) - Gasser, Stephan; Lim, Lina H K; Cheung, Florence S G
Abstract : Recent success in immunomodulating strategies in lung cancer and melanoma has prompted much enthusiasm in their potential to treat other advanced solid malignancies. However, their applications have shown variable success and are even ineffective against some tumours. The efficiency of immunotherapies relies on an immunogenic tumour microenvironment. The current field of cancer immunology has focused on understanding the interaction of cancer and host immune cells to break the state of immune tolerance and explain how molecular patterns of cytokines and chemokines affect tumour progression. Here, we review our current knowledge of how inherent properties of tumours and their different tumour microenvironments affect therapeutic outcome. We also discuss insights into recent multimodal therapeutic approaches that target tumour immune evasion and suppression to restore anti-tumour immunity.